The inflammatory response, a mixed blessing for muscle homeostasis and plasticity - Bouredji, Zineb; Argaw, Anteneh; Frenette, Jérôme (Frontiers in Physiology, 2022)
Skeletal muscle makes up almost half the body weight of heathy individuals and is involved in several vital functions, including breathing, thermogenesis, metabolism, and locomotion. Skeletal muscle exhibits enormous plasticity with its capacity to adapt to stimuli such as changes in mechanical loading, nutritional interventions, or environmental factors (oxidative stress, inflammation, and endocrine changes). Satellite cells and timely recruited inflammatory cells are key actors in muscle homeostasis, injury, and repair processes. Conversely, uncontrolled recruitment of inflammatory cells or chronic inflammatory processes leads to muscle atrophy, fibrosis and, ultimately, impairment of muscle function. Muscle atrophy and loss of function are reported to occur either in physiological situations such as aging, cast immobilization, and prolonged bed rest, as well as in many pathological situations, including cancers, muscular dystrophies, and several other chronic illnesses. In this review, we highlight recent discoveries with respect to the molecular mechanisms leading to muscle atrophy caused by modified mechanical loading, aging, and diseases. We also summarize current perspectives suggesting that the inflammatory process in muscle homeostasis and repair is a double-edged sword. Lastly, we review recent therapeutic approaches for treating muscle wasting disorders, with a focus on the RANK/RANKL/OPG pathway.